The relationship between physical exercise and problematic internet use in college students: the chain-mediated role of self-control and loneliness - Junshuai Xu; Liuquan Tang (BMC Public Health, 2024)
Abstract Objective From the perspective of exercise psychology, to investigate the antefacts of problematic internet use (PIU) in college students, and to reveal the chain mediating effect of self-control and loneliness between physical exercise and PIU. Methods 1081 college students in Chongqing, China were investigated by Physical Activity Rating Scale (PARS-3), Self-control Scale (SCS), Loneliness Scale (UCLA), and Internet Addiction Scale (CIAS-R), and the data were statistically analyzed by SPSS25.0 and AMOS21.0 software. Results (1) There was a significant negative correlation between physical exercise and PIU, and the former has a direct negative predictive effect on the latter. (2) Physical exercise could indirectly influence the PIU of college students through the partial mediating effect of self-control and loneliness, respectively. (3) Physical exercise could also indirectly influence PIU through the chain mediation of “self-control → loneliness”. Conclusion Maintaining regular physical exercise can promote the improvement of self-control and the weakening of the loneliness experience of college students, and then help to prevent or alleviate PIU behavior, which is of great significance for psychological and behavioral health.